2020
DOI: 10.1111/jocn.15260
|View full text |Cite
|
Sign up to set email alerts
|

“Please mind the gap”: A secondary analysis of discomfort and comfort in intensive care

Abstract: Aims and objectives To explore in depth discomfort in intensive care as experienced by patients and attended to by critical care nurses. Background Discomfort in illness is complex and persistent, and its alleviation is a challenge for nurses working in intensive care units (ICU). In previous studies, we showed that ICU patients described little actual pain but suffer from much discomfort. Critical care nurses had a systematic approach to the treatment of pain, but were more haphazard in dealing with other typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 60 publications
1
18
0
1
Order By: Relevance
“…The reported minor complications such as discomfort, excessive secretions, stomal air leak, burping, subglottic air trapping, retching, and nausea [6][7][8]15,19,24 will seldom override the benefits of the ability to speak in this population. Patient discomfort may be inevitable in intensive care 28 and should not necessarily be categorised as a complication or problem in relation to safety, but rather identified as an area in which comfort may be enhanced. The inability to communicate may in itself contribute to patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported minor complications such as discomfort, excessive secretions, stomal air leak, burping, subglottic air trapping, retching, and nausea [6][7][8]15,19,24 will seldom override the benefits of the ability to speak in this population. Patient discomfort may be inevitable in intensive care 28 and should not necessarily be categorised as a complication or problem in relation to safety, but rather identified as an area in which comfort may be enhanced. The inability to communicate may in itself contribute to patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to communicate may in itself contribute to patient discomfort. 28 Facilitating speech may enhance safety, comfort, and quality of care, by enabling both self-expression and communication of symptoms to HCP. 27,29 The most serious adverse events described were subcutaneous emphysema, 18 and cuff rupture following an incorrect procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are affected by critical illness continue to live their lives in a multifaceted way and exploring their lifeworld can increase and give depth to their experiences. Patients’ stories from ICU have been widely studied in previous decades, describing memories of chaos, dreams and hallucinations, fear, pain, and other discomforts ( Berntzen et al, 2020 ; Cutler et al, 2013 ; Egerod et al, 2015 ; Sanson et al, 2021 ; Uotinen, 2011 ). In a synthesis of Nordic research, Egerod et al (2015) reported how the experience of suffering was evident in intensive care, even though measures had been implemented to improve and make intensive care treatment more humane.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kolcaba's comfort theory, when the disease deprives the integrity of the patient's body or deprives the normal functioning of the brain and body functions, the patient can have a strong demand for treatment and comfort due to all the current experience ( 10 ). But in the regular care mode, there is a gap between the patient's comfort needs and the caregivers meeting their needs, and there is a gap between the effect of hospital nursing and the effect of out-of-hospital nursing.…”
Section: Discussionmentioning
confidence: 99%